2014
DOI: 10.2147/ijn.s57936
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of SiO2 or ZnO nanoparticles with different sizes and surface charges on U373MG human glioblastoma cells

Abstract: Silicon dioxide (SiO 2 ) and zinc oxide (ZnO) nanoparticles are widely used in various applications, raising issues regarding the possible adverse effects of these metal oxide nanoparticles on human cells. In this study, we determined the cytotoxic effects of differently charged SiO 2 and ZnO nanoparticles, with mean sizes of either 100 or 20 nm, on the U373MG human glioblastoma cell line. The overall cytotoxicity of ZnO nanoparticles against U373MG cells was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In contrast, 200 nm aSiNPs did not show any toxicity even at relatively high concentrations. Kim et al 66 determined the cytotoxicity of aSiNPs with mean sizes of either 20 nm or 100 nm in human glioblastoma cell line (U373MG). The results indicated that the 20 nm nanoparticles were more toxic than the 100 nm nanoparticles.…”
Section: Size-dependent Cytotoxicity Of Asinps On Cell Lines From Kidmentioning
confidence: 99%
“…In contrast, 200 nm aSiNPs did not show any toxicity even at relatively high concentrations. Kim et al 66 determined the cytotoxicity of aSiNPs with mean sizes of either 20 nm or 100 nm in human glioblastoma cell line (U373MG). The results indicated that the 20 nm nanoparticles were more toxic than the 100 nm nanoparticles.…”
Section: Size-dependent Cytotoxicity Of Asinps On Cell Lines From Kidmentioning
confidence: 99%
“…This observation is consistent with the previously published work where neither the size nor the surface charge of the ZnO nanoparticles affected their cytotoxicity against U373MG cells. 53 However, we do not exclude the possibility that the short length of CNCs derivative may contribute to less nanomaterial agglomeration or cell clustering formation around the CNCs and therefore better distribution onto the cell surface, resulting in less cytotoxicity.…”
Section: Resultsmentioning
confidence: 93%
“…While charge is thought to be a highly influential factor in determining particle internalization, little consensus has been achieved to determine whether positive, negative or neutral charge facilitates or hinders particle internalization (Ayala et al, 2013; Bahmani et al, 2011; Harush-Frenkel et al, 2007; He et al, 2010; Kim et al, 2014; Wilhelm et al, 2003). Part of the difficulty in reaching consensus is the lack of consistency among testing conditions for various studies: chemistry of bead production, cell culture conditions and in vivo techniques are highly variable and can yield vastly different results for any given particle and cell type.…”
Section: Discussionmentioning
confidence: 99%